1987
DOI: 10.1002/jcp.1041320321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the mi allele on mast cells, basophils, natural killer cells, and osteoclasts in C57BI/6J mice

Abstract: The osteopetrotic, microphthalmic (mi/mi) mouse lacks functional osteoclasts and has also been reported to be deficient in mast cells and natural-killer (NK) cells. The later deficiencies could be secondary to the osteopetrotic marrow, or a direct result of the mi allele. Therefore, heterozygotes were examined for these cell types, since these mice do not exhibit osteopetrosis. Adult +/mi animals have approximately 50%, and mi/mi animals examined by histologic techniques or tissue histamine levels have 0-10%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(53 citation statements)
references
References 29 publications
0
53
0
Order By: Relevance
“…PU.1, GATA-2, GATA-3, and the microphthalmia-associated transcription factor are essential for mast cell development [22][23][24][25]. We showed that adiposederived CFCs express these four transcription factors as peritoneal cell-derived mast cell controls (Fig.…”
Section: Adipose Tissue Harbors Mast Cell Progenitors and Precursorsmentioning
confidence: 89%
“…PU.1, GATA-2, GATA-3, and the microphthalmia-associated transcription factor are essential for mast cell development [22][23][24][25]. We showed that adiposederived CFCs express these four transcription factors as peritoneal cell-derived mast cell controls (Fig.…”
Section: Adipose Tissue Harbors Mast Cell Progenitors and Precursorsmentioning
confidence: 89%
“…MITF is expressed in melanocytes, in retina pigment cells, in mast cells and in osteoclasts (50,51). Pigmentation defects in mi mice seem to be a result of the absence of melanocytes.…”
Section: Camp-dependent Intracellular Pathways Involved In the Regulamentioning
confidence: 99%
“…The mi-MITF is defective in the DNA binding activity and the nuclear localization potential, and it does not transactivate target genes Takebayashi et al, 1996;Tsujimura et al, 1996;Jippo et al, 1997;Ito et al, 1998;Kim et al, 1998). The mi/mi mice show microphthalmia, depletion of pigment in both hair and eyes, osteopetrosis, and decrease of mast cells (Silvers, 1979;Green, 1981;Stevens and Loutit, 1982;Stechschulte et al, 1987). In addition to the decrease in number, the phenotype of mast cells is abnormal in mi/mi mice (Ebi et al, 1990(Ebi et al, , 1992Kasugai et al, 1993;Isozaki et al, 1994;Jippo et al, 1994).…”
Section: Introductionmentioning
confidence: 99%